Medication-Related Burden among Patients with Chronic Disease Conditions: Perspectives of Patients Attending Non-Communicable Disease Clinics in a Primary Healthcare Setting in Qatar - Amani Zidan; Ahmed Awaisu; Maguy Saffouh El-Hajj; Samya Ahmad Al-Abdulla; Dianne Candy Rose Figueroa; Nadir Kheir (MDPI AG, 2018)
This study aimed to assess perceived medication-related burden among patients with multiple non-communicable diseases (NCDs) and to investigate the association between perceived burden and adherence to medication therapy. Using a cross-sectional study in three primary care clinics in Qatar, medication-related burden was measured using the Living with Medicines Questionnaire (LMQ) among adults with diabetes, with or without other comorbidities. Adherence was measured using the Adherence to Refills and Medications Scale (ARMS). Two hundred and ninety-three eligible patients participated in the study. The majority of them reported experiencing minimal (66.8%) to moderate (24.1%) medication-related burden. There was a significant positive correlation between the scores of the LMQ (medication-related burden) and ARMS (medication adherence), rs (253) = 0.317, p < 0.0005.